Risk Control Strategy In Seed Management Contracts By Pt East West Seed Indonesia Jember Region - Nurul Hidayat; Nikmatul Masruroh; Ahmadiono Ahmadiono (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2025)
The development of agribusiness in Indonesia has opened a new discourse in agribusiness practices carried out primarily by farmers or cultivators. One form of agribusiness that is quite widely carried out is the partnership concept. Several companies try to offer this partnership concept to farmers to produce a certain commodity and guarantee the marketing of their products. The concept and pattern of partnership offered by one company to another varies. Several factors that influence the concept and pattern of partnership are the type of commodity cultivated, consumer demand for the cultivated commodity, and the market share of the cultivated commodity. PT East West Seed Indonesia (Ewindo) is the first integrated vegetable seed company in Indonesia that has a commitment to being the best Farmer's Friend. The research focuses on: 1) How is the seed management contract at PT East West Seed Indonesia in the Jember Region? 2) How is the identification of forms of risk control in the seed management contract by PT East West Seed Indonesia in the Jember Region? This type of research is descriptive qualitative research with the researcher's own key instrument. The research location is at PT East West Seed Indonesia in Gumuksari, Tegal Besar, Kec. Kaliwates, Jember Regency, East Java. Data collection used interview, documentation, and observation methods. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The data sources obtained consisted of primary and secondary data sources. The results of this study indicate that: First, the seed management contract implemented by PT East West Seed Indonesia (Ewindo) in the Jember region demonstrates a highly structured and calculated modern agribusiness partnership model. Based on the findings, the company does not diversify the contract model, but instead adopts a uniform and binding nucleus-plasma partnership framework. This structure is built on the principle of strict reciprocity, where the rights and obligations of both parties (the company and the farmers) are clearly defined to minimize risk and uncertainty (gharar). Second, the identification of forms of risk control in the seed management contract by PT East West Seed Indonesia (Ewindo) in Jember demonstrates a comprehensive and layered risk management architecture. From the company's perspective, risk control is designed proactively through the systematic identification of four main areas: technical-quality, agronomic production, operational-behavioral, and market.